(untitled) (European Journal of Economics, Finance and Business Development, 2025)
A number of scientific researches related to the field have been studied in researching the ways of developing ecological tourism in Uzbekistan. List of areas where ecotourism services will be established in state reserves, nurseries, national nature parks and forestry and list of major water bodies in Uzbekistan where beach and water recreation tourism services are organized, are analyzed. Conclusions and proposals are developed based on the conducted research.